Problem based learning: a teaching strategy for teaching in information and documentation sciences - Dos Santos, Beatriz Rosa Pinheiro [UNESP]; Moro Cabero, María Manuela; Damian, Ieda Pelógia Martins (Universidad Nacional de La Plata, 2023)
The research focuses on the search for pedagogical strategies to apply in the learning of contents and the acquisition of competences and abilities in the scientific area of information and documentation. The purpose is to facilitate the acquisition of practical skills of its graduates that favor their labor insertion. It focuses on the confluence between knowledge management and learning through active teaching and more specifically on problem-based learning. It is intended to answer the following question: How can Problem Based Learning contribute to optimal pedagogical practice in the teaching of information and documentation sciences? The following objectives have been formulated: firstly, to define and identify conceptual elements and criteria for the use of Problem Based Learning; secondly, to analyze the presence of the Problem Based Learning foundations in a current study plan, as is the case under study, and thirdly, to verify its operability in terms of student satisfaction with active teaching models. An exploratory-descriptive methodology is used, using Bardin's analysis for data analysis. The main results highlight that the application of problem-based learning in the field of information and documentation favors the acquisition of practical skills and promotes the job placement of graduates. In addition, they provide a solid foundation for optimal pedagogical practice in the field of iation and documentation sciences, fostering the development of relevant skills for professional practice.
Aprendizaje basado en problemas: una estrategia pedagógica para la enseñanza en las ciencias de la información y documentación
Keywords: Active methodologies; Knowledge management; Pedagogical strategies; Problem based learning; Spain; Teaching of information sciences